Environmental exposure of wild carnivores to zoonotic pathogens: Leptospira infection in the first free living wolf (canis lupus linnaeus, 1758) found dead in the friuli venezia giulia region - Bregoli M.; Pesaro S.; Ustulin M.; Vio D.; Beraldo P.; Galeotti M.; Cocchi M.; Lucchese L.; Bertasio C.; Boniotti M. B.; Lapini L.; Natale A. (International Journal of Environmental Research and Public Health, 2021)
Leptospirosis is a worldwide-spread zoonosis causing disease and death in dogs and in humans. A Leptospiral infection has been recorded in several wild carnivore species in Europe, but tissue pathological changes were not commonly described. The Grey wolf (Canis lupus) has been expanding its distribution range in north-eastern Italy during the last decade. A young wolf, repre-senting the first individual handled in the region, was found road-killed and then submitted to necropsy. Pathological changes included erosive lesions of gingival mucosa, mild liver enlargement, and multifocal degenerative-necrotic areas along with hyperemic reactive lesions; multifocal inter-stitial nephritis and multifocal lung hemorrhages were observed. A Polymerase Chain Reaction (PCR) able to detect pathogenic species of Leptospira performed on a kidney sample was positive. Serological reactions for serogroup Gryppotyphosa (1:6400), Pomona (1:800), and Icterohaemor-rhagiae (1:200) were evidenced by MAT. Genotyping by Multilocus Sequence Typing (MLST) performed on detected Leptospira characterized it as belonging to Sequence Type (ST) 117, which refers to L. kirschneri, serogroup Pomona, serovar Mozdok. Regardless of the role of Leptospira infection as an eventual predisposing factor to the road killing of this wolf, to the best of the authors’ knowledge, this is the first report of Leptospira-induced pathology in a wolf in Europe. Surveys on Leptospira infection in free-ranging wildlife species should be pursued in order to achieve further epidemio-logical knowledge on the circulation of the Leptospira strain.